From ‘Forbidden’ Conjugal Love to Infidelity. Adultery in Italian Summae Confessorum (14th-16th Century) (Italian Review of Legal History, 2015)
In Italy, as in most of the civilized world, adultery is no longer considered criminally relevant behavior. Its decriminalization had long been a goal, and although that goal has largely been achieved, civil law continues to provide for it today. Yet in the age when adultery was punishable by canon and civil law – which included it as a criminal act – both morality and religion played leading roles in mutually influencing legal norms. Specifically, this article shall examine the stance on adultery expressed in the Summae confessorum published in the Italian area between the fourteenth and sixteenth centuries.
Keywords: adultery; marriage; Summae confessorum 14th-16th century; separation